2002
DOI: 10.1099/00221287-148-11-3725
|View full text |Cite
|
Sign up to set email alerts
|

YlBMH1 encodes a 14-3-3 protein that promotes filamentous growth in the dimorphic yeast Yarrowia lipolytica a aThe GenBank accession numbers for the YlBMH1 and YlBMH2 sequences reported in this study are AY090661 and AY090662, respectively.

Abstract: Most pathogenic fungi have the ability to alternate between a unicellular yeast form and different filamentous forms (hyphae and pseudohyphae). This attribute is generally regarded as an important virulence factor and has also attracted attention because of its implications in the study of eukaryotic cell differentiation. To identify genes that are involved in the regulation of these events, chemical mutagenesis of the dimorphic yeast Yarrowia lipolytica was performed and morphological mutants that were unable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
2
17
1
Order By: Relevance
“…14-3-3 proteins have also been implicated in controlling filamentation in other dimorphic fungi, especially in C. albicans (37) and Y. lipolytica (16). In these organisms, the extent of filamentous growth is proportional to the level of 14-3-3 protein expression (16). More importantly, 14-3-3 proteins have also been shown to be essential for viability in S. cerevisiae (38), C. albicans (9), and S. pombe (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14-3-3 proteins have also been implicated in controlling filamentation in other dimorphic fungi, especially in C. albicans (37) and Y. lipolytica (16). In these organisms, the extent of filamentous growth is proportional to the level of 14-3-3 protein expression (16). More importantly, 14-3-3 proteins have also been shown to be essential for viability in S. cerevisiae (38), C. albicans (9), and S. pombe (19).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in S. cerevisiae, 14-3-3 homologues Bmh1/Bmh2 regulate pseudohypha formation through the MAPK pathway (38). 14-3-3 proteins have also been implicated in controlling filamentation in other dimorphic fungi, especially in C. albicans (37) and Y. lipolytica (16). In these organisms, the extent of filamentous growth is proportional to the level of 14-3-3 protein expression (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these microorganisms, the filamentous growth is proportional to the level of expression of the 14-3-3 protein. 38 Studies have shown that the variability of cell size within a fungal cell population alters pathogenicity via altering phagocytosis. 43,44 Phagocytosis, along with the resultant killing by macrophages and monocytes in the lungs, is one of the first lines of defense by the host immune system, 45 thus demonstrating that in P. brasiliensis, a decrease in cell size leads to increased phagocytosis and decreased virulence 44 .…”
Section: Discussionmentioning
confidence: 99%
“…37 Morphological transitions in dimorphic fungi are highly complex events triggered by a wide range of environmental factors and consisting of a reversible change in the growth pattern, alternating between the unicellular yeast form and the filamentous form (hyphae and pseudohyphae). 38 Understanding the mechanisms that regulate these events is of extreme interest due to implications for pathogenesis and cell differentiation, as observed with the inhibition of the transition to the parasitic form by the female hormone estrogen. 39 The proteins Bmph1p and Bmph2p in Saccharomyces cerevisiae are homologous to Pb14-3-3 and regulate pseudohyphal growth through the MAPK (mitogen-activated protein kinase) signaling pathway.…”
Section: Discussionmentioning
confidence: 99%